2019
DOI: 10.1111/jvh.13048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of miR‐520e‐mediated MAPK signalling pathway on HBV replication and regulation of hepatocellular carcinoma cells via targeting EphA2

Abstract: Summary We determined the role of miR‐520e in the replication of hepatitis B virus (HBV) and the growth of hepatocellular carcinoma (HCC) cells. MiR‐520e and EPH receptor A2 (EphA2) in HBV‐positive HCC tissues and cells were detected, and we studied the impact of miR‐520e and the EphA2 receptor in cellular and murine HBV replication models. We find that MiR‐520e was upregulated and EphA2 was downregulated in HBV‐positive HCC tissues and cells. MiR‐520e was decreased in Huh7‐X and HepG2‐X cells in which HBx was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…Wang et al [ 51 ] showed that miR-302a inhibits cell proliferation and promotes the apoptosis of human HCC cells by targeting MAP3K2 and PBX3 to reduce the expression of the key MAPK-associated proteins, including phosphorylated ERK (p-ERK1/2), p38 (p-p38), and JNK (p-JNK). Further, Tian et al [ 52 ] demonstrated that a decrease in miR-520e expression was observed in HBV-positive HCC cells and tissues. Further studies have revealed that miR-520e overexpression specifically inhibited EPH receptor A2 (EphA2), thereby blocking the p38 MAPK and ERK1/2 signaling pathways.…”
Section: Microrna Related To the Mapk Signaling Pathway In Liver Cancermentioning
confidence: 99%
“…Wang et al [ 51 ] showed that miR-302a inhibits cell proliferation and promotes the apoptosis of human HCC cells by targeting MAP3K2 and PBX3 to reduce the expression of the key MAPK-associated proteins, including phosphorylated ERK (p-ERK1/2), p38 (p-p38), and JNK (p-JNK). Further, Tian et al [ 52 ] demonstrated that a decrease in miR-520e expression was observed in HBV-positive HCC cells and tissues. Further studies have revealed that miR-520e overexpression specifically inhibited EPH receptor A2 (EphA2), thereby blocking the p38 MAPK and ERK1/2 signaling pathways.…”
Section: Microrna Related To the Mapk Signaling Pathway In Liver Cancermentioning
confidence: 99%
“…EPHA2 has been reported to be associated with mitogen activated protein kinase (MAPK) pathways. Jing-Hui et al reported that overexpression of microRNA miR-520e inhibited p38MAPK and ERK1/2 signaling pathways through inhibition of EPHA2, ultimately leading to the suppression of cell proliferation in hepatocellular carcinoma [ 31 ]. EPHA2 is able to induce EMT in gastric cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promoted EPHA2 expression in cancer cells is linked to a dismal prognosis because of recurrence as a consequence of enhanced metastasis [28]. As for its upstream miRNAs, EPHA2 has been indicated to be targeted by different miRNAs to participate the development of various cancers, including non-small cell lung cancer [29], hepatocellular carcinoma [30] as well as colorectal cancer [31]. After the validation of the targeting relationship between EPHA2 and miR-451a in BCa cells, we carried out rescue experiments again.…”
Section: Discussionmentioning
confidence: 99%